Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
x = 2
Step-by-step explanation:
3x² - 2x(x + 1) = x² + x - 6 ← distribute and simplify left side
3x² - 2x² - 2x = x² + x - 6
x² - 2x = x² + x - 6 ( subtract x² + x from both sides )
- 3x = - 6 ( divide both sides by - 3 )
x = 2
Step-by-step explanation:
3x^2-2x(x+1) = x^2 +x-6
3x^2−2x(+1)=x^2+xx−6
3x^2−2x^2−2x=x^2+x−6
3x^2−2x^2-2x=x^2+x−6
1x^2-2x=x^2+x-6
1x^2−2x=x^2+x−6
x^2−2x=x^2+−6
solution:
x=2
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.